2020
DOI: 10.1021/acs.est.0c02833
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Nutrients from Dairy Wastewater by Extremophilic Microalgae with High Ammonia Tolerance

Abstract: This study explored the possibility of incorporating extremophilic algal cultivation into dairy wastewater treatment by characterizing a unique algal strain. Results showed that extremophilic microalgae Chlorella vulgaris CA1 newly isolated from dairy wastewater tolerated a high level of ammonia nitrogen (2.7 g/L), which was over 20 times the ammonia nitrogen that regular Chlorella sp. could tolerate. The isolate was mixotrophically cultured in dairy effluent treated by anaerobic digestion (AD) for recycling n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 75 publications
(140 reference statements)
0
9
0
Order By: Relevance
“…Recently, it has been recognized that wastewater could act as a vital nutrient provider for microalgae, witnessing the potential of using microalgae against wastewater treatment [ 23 , 53 , 54 ]. Owing to unique biological characteristics, microalgae often could grow well in various wastewater with high nutrient utilization and efficiently convert these nutrients into various value-added biomolecules [ [55] , [56] , [57] ].…”
Section: Why Use Immobilized Microalgal Wastewater Treatment Systems?mentioning
confidence: 99%
“…Recently, it has been recognized that wastewater could act as a vital nutrient provider for microalgae, witnessing the potential of using microalgae against wastewater treatment [ 23 , 53 , 54 ]. Owing to unique biological characteristics, microalgae often could grow well in various wastewater with high nutrient utilization and efficiently convert these nutrients into various value-added biomolecules [ [55] , [56] , [57] ].…”
Section: Why Use Immobilized Microalgal Wastewater Treatment Systems?mentioning
confidence: 99%
“…For instance, potential microalgae were isolated from dairy effluents. During this stage, effluent samples were cultivated in artificial media such as BG-11 or BBM [109,110]. Because many of the processes are performed with commercial strains, an adaptation step is necessary before cultivation.…”
Section: Dairy Processing Wastewatermentioning
confidence: 99%
“…Microalgal bioremediation is one of the promising alternatives to conventional technologies due to its competitive advantages such as nutrient recycling with simultaneous production of value-added biomass. However, its industrialization was largely limited by unstable microalgal activities in the MW treatment plant (MWTP), which experienced an abrupt change in nutrient loadings due to the fluctuations in both wastewater quality and quantity. Particularly, the periodic high-ammonium (NH 4 + -N) strength accompanied by the influent would lead to unsatisfactory microalgal growth and even the failure of the entire system. , …”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the periodic high-ammonium (NH 4 + -N) strength accompanied by the influent would lead to unsatisfactory microalgal growth and even the failure of the entire system. 9,10 Our recent study demonstrated that free ammonia (FA), produced by NH 4 + -N and pH in high NH 4 + -N-strength wastewater, acted as the primary stress factor for the decreased microalgal activities. 11 However, the FA shock inhibition mechanism and subsequent microalgal self-adaptive regulations remain unclear, impeding potential improvement of microalgal treatment performance.…”
Section: Introductionmentioning
confidence: 99%